Metode Fuzzy Time Series Cheng dalam Memprediksi Jumlah Wisatawan di Provinsi Sumatera Barat - Eka Pandu Cynthia; Rahma wati (Faculty of Teacher Training and Education, 2019)
West Sumatra Province is one of the provinces in Indonesia that is very rich in its natural beauty, making this area one of the popular tourist destinations for local and foreign tourists. The large number of tourists who come has a very good impact on the Province of West Sumatra, especially for the economic sector. Increased regional income and growing economic activity of the community is very much influenced by the presence of these tourists. In this study, the author uses one method to make predictions or forecasting, namely the Cheng Fuzzy Time Series method. The actual data used is the number of tourists from 2015 to 2017, and the process of predicting the number of tourists will be carried out for 2019 until 2021. From the results of calculations that have been done using this method, good performance conclusions are generated, in the range of MAPE 10% - 20%, which is an error value of 14.61%. With an absolute error value of 5.26 and the value of predictive accuracy is 85.39%.